2011
DOI: 10.1186/1472-6920-11-27
|View full text |Cite
|
Sign up to set email alerts
|

The influence of longitudinal mentoring on medical student selection of primary care residencies

Abstract: BackgroundThe number of students selecting careers in primary care has declined by 41% in the last decade, resulting in anticipated shortages.MethodsFirst-year medical students interested in primary care were paired with primary care mentors. Mentors were trained, and mentors and students participated in focus groups at the end of each academic year. Quantitative and qualitative results are presented.ResultsStudents who remained in the mentoring program matched to primary care programs at 87.5% in the first ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…On average, data from that study showed that one third more students, starting with an initial interest in primary care, actually entered primary care fields when they received mentoring from primary care physicians. These students had a better idea of the nature of primary care, had an increased respect for the field, and recognized the impact of health disparities on patients and their physicians (5). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, data from that study showed that one third more students, starting with an initial interest in primary care, actually entered primary care fields when they received mentoring from primary care physicians. These students had a better idea of the nature of primary care, had an increased respect for the field, and recognized the impact of health disparities on patients and their physicians (5). …”
Section: Discussionmentioning
confidence: 99%
“…Many factors contribute to one's decision with regards to motivation and reason to choose a specific medical specialty. Whether one chooses a specific specialty due to advice from friends or family, admiration of a certain mentor or genuine interest in the specialty, there are many incentives and factors that converge to result in the final decision (15). While motivations do vary according to specialties, they may include lifestyle choices, a possibility of private practice, an interest in specific diseases, a varied scope of practice, an interest in research and teaching, or to gain a higher income (2, 4, 68).…”
Section: Introductionmentioning
confidence: 99%
“…1 Most formalised mentoring programmes for medical students have been reported from the USA, but also from Germany, Switzerland, Canada, the Netherlands and the UK. 1,[3][4][5][6][7] Both formal and informal mentorship has been reported and the definition of mentor and mentoring varies, 1,8 which sometimes makes it difficult to interpret the literature in the field. This paper contributes a deeper understanding of the meaning of continuous group and one-to-one mentoring, based on medical students´ experiences.…”
Section: Introductionmentioning
confidence: 99%
“…We know from prior research that family medicine role models and mentors can influence medical student interest in family medicine. [21][22][23] Future research exploring the influence of senior medical school administrators on career choice is needed to better understand the nature of this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…20 Mentoring appears to support students with a primary care interest to graduate into a primary care residency. 21 Having a family medicine role model or family medicine faculty advisor significantly recruits and retains medical students' interest in family medicine. 22,23 Realization of the broad scope of practice for a family physician can also prompt students to consider a career in family medicine.…”
Section: Introductionmentioning
confidence: 99%